High-thermal-insulation wear-resistant rubber and preparation method thereof
By using thermally resistant wear-resistant fillers with hydrophobic porous alumina hollow spheres and branched silica in nitrile rubber, the shortcomings of existing materials in thermal wear resistance are solved, efficient heat insulation and wear resistance are achieved, and the overall performance of the material is improved.
Patent Information
- Application Number
- CN202411766813.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
The existing nitrile rubber materials have shortcomings in thermal insulation and wear resistance, making it difficult to effectively isolate heat transfer and improve wear resistance.
The thermally insulated wear-resistant filler composited with hydrophobic porous alumina hollow spheres and branched silica is used to improve the low thermal conductivity and durability of the material by forming a multi-layered thermal insulation structure and skeleton support, and improve the wear resistance of the material through hydrophobic and spherical particle structures.
It realizes the low thermal conductivity and wear resistance of high-temperature wear-resistant rubber, effectively reducing heat transfer and wear, and improving the stability and service life of the material.
Smart Images

Figure BDA0005169162140000101 
Figure BDA0005169162140000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional rubber materials, and in particular to a high-heat-insulating and wear-resistant rubber and a preparation method thereof. Background Art
[0002] With the intensification of the global energy crisis and the improvement of environmental awareness, thermal insulation has become an important measure to save energy. Nitrile rubber (NBR) is a rubber material with excellent comprehensive performance, with good oil resistance, heat resistance, corrosion resistance, ozone resistance, resistance to compression permanent deformation, high strength, high tearing and other properties. With the continuous development of rubber materials, especially the advancement of synthetic rubber technology, people have higher requirements for the improvement of the functionality of nitrile rubber. High thermal insulation and wear resistance is one of the important properties. Thermal insulation and wear-resistant rubber has low thermal conductivity, which can effectively isolate heat transfer and reduce energy loss, thus helping to reduce energy consumption, especially in the fields of construction and industry, and has therefore received widespread attention. Summary of the invention
[0003] Technical problem to be solved: In view of the above technical problems, the purpose of the present invention is to provide a high thermal insulation and wear-resistant rubber and a preparation method thereof, which adopts a thermal insulation and wear-resistant filler compounded with hydrophobic porous alumina hollow balls and dendritic silica. The hydrophobic porous alumina hollow balls and dendritic silica can form a multi-level thermal insulation structure. The hydrophobic porous alumina hollow balls can effectively prevent the conduction of heat due to the hollow air-filled structure, and the thermal conductivity is very low. At the same time, its hydrophobic properties can protect it from the influence of moisture and maintain a stable low thermal conductivity. The dendritic silica can serve as a skeleton support to maintain the overall stability and durability of the low thermal conductivity.
[0004] Technical solution: A highly heat-insulating and wear-resistant rubber, comprising the following components in parts by weight: 100 parts of nitrile rubber Zinc oxide 5 parts 2 parts stearic acid 0.5 parts of microcrystalline wax 20-35 parts of thermal insulation and wear-resistant filler Anti-aging agent RD 2 parts Anti-aging agent 4451 parts Accelerator TMTD 2 parts 1 part sulfur; The heat-insulating and wear-resistant filler is a composite of hydrophobic porous alumina hollow balls and dendritic silicon dioxide. Furthermore, the mass ratio of the hydrophobic porous alumina hollow spheres to the dendritic silica is 3:(1-4). Furthermore, the preparation method of the hydrophobic porous alumina hollow spheres is as follows: (1) Take 200 mL of deionized water, 80 mL of anhydrous ethanol and 1 mL of aqueous ammonia, stir at 30-45° C. for 60 min, add 1.4 g of phenol, 2.8 mL of formaldehyde, 0.6 g of lignin, 0.1 mL of aqueous ammonia and 0.45 g of polyvinyl alcohol, heat to 95° C. for 15 h while stirring, add 0.34 g of hexamethylenetetramine, stir for 3 h, filter and separate, wash with water and dry; (2) placing in a tubular furnace, calcining in a nitrogen atmosphere, heating to 300°C at a heating rate of 2°C / min, keeping the temperature for 30 min, and then heating to 800-1000°C at a heating rate of 5°C / min, keeping the temperature for 2 h, to obtain porous carbon spheres; (3) Take 60 mL of 0.4 mol / L aluminum nitrate ethanol solution, add 0.2 g of porous carbon spheres, sonicate for 20 min, let stand for 8 h, filter and dry; (4) placing in a tube furnace, heating to 350°C and keeping the temperature for 2 h, then heating to 600°C and keeping the temperature for 4 h, and then cooling to obtain porous alumina hollow spheres; (5) Take 5 g of porous alumina hollow balls and 0.1-0.3 g of polymethylhydrogensiloxane, mix them evenly and add them into a ball mill, use steel balls as the ball milling medium, set the main disk frequency at 40 Hz, and ball mill for 30 min; (6) The product was repeatedly washed with petroleum ether, centrifuged until there was no free polymethylhydrogensiloxane in the supernatant, and vacuum dried at 60° C. to obtain hydrophobic porous alumina hollow spheres. Furthermore, in step (5), the balls used for ball milling are: 1 Φ20 mm steel ball, 5 Φ10 mm steel balls, and 10 Φ6 mm steel balls. Furthermore, the preparation method of the dendritic silica is as follows: (1) Dissolve 30 g of polyvinyl pyrrolidone in 320 mL of n-pentanol, add 28 mL of ethanol and 8 mL of water, shake evenly, then drop 3 mL of 0.18 mol / L sodium citrate dihydrate aqueous solution and mix evenly; (2) Add 5.5 mL of ammonia water while shaking, let it stand for 5 min, then add 2.8 mL of ethyl orthosilicate, shake evenly, and place at 90°C to react for 2-3 h; (3) filtering with a polytetrafluoroethylene membrane, washing with ethanol and water respectively, and then drying to obtain linear silica; (4) Take 2 g of linear silica, add 20 mL of ethanol and 6 mL of deionized water, add 0.22 g of dopamine hydrochloride, and adjust the pH to 8.5 with tris(hydroxymethyl)aminomethane; (5) Add 2 mL of ethyl orthosilicate and let stand at 30 °C for 24 h; (6) Filter with a polytetrafluoroethylene membrane, wash with ethanol and water respectively, and then dry to obtain dendritic silica. Furthermore, the pore size of the polytetrafluoroethylene membrane in step (3) and step (6) is 0.45 μm. The method for preparing the above-mentioned high heat-insulating and wear-resistant rubber comprises the following steps: S1: After refining the raw nitrile rubber, zinc oxide, stearic acid, microcrystalline wax, antioxidant RD and antioxidant 445 are added and mixed and refining is performed for 3-4 minutes; S2: Add the heat-insulating and wear-resistant filler into the open milling system in two batches and mix them evenly; S3: Add accelerator TMTD and sulfur, make triangle packs for multiple cycles, and then thin out the sheets 5-6 times, and place them for 12 hours to obtain the mixed rubber; S4: Put the mixed rubber into a flat mold and vulcanize it with a flat vulcanizer. The vulcanization temperature is 160°C and the vulcanization time is 15-30 minutes to obtain high heat-insulating and wear-resistant rubber. Furthermore, the refining temperature in S1 is 50°C. Beneficial effects: 1. The present invention adopts a heat-insulating and wear-resistant filler compounded with hydrophobic porous hollow alumina balls and dendritic silica. The hydrophobic porous hollow alumina balls and dendritic silica can form a multi-layered heat-insulating structure. The hydrophobic porous hollow alumina balls can effectively prevent the conduction of heat due to the hollow air-filled structure, and the thermal conductivity is very low. At the same time, its hydrophobic property can protect it from the influence of moisture and maintain a stable low thermal conductivity. The dendritic silica can serve as a skeleton support to maintain the overall stability and durability of the low thermal conductivity. 2. The hydrophobic porous alumina hollow spheres and dendritic silica of the present invention can cooperate to entangle to form a hard protective layer. When subjected to friction, the hydrophobic porous alumina hollow spheres provide lubricity, and the dendritic silica arranged parallel to the direction of the friction provides an axial force to enable the polymer film to maintain its original chain motion ability. The dendritic silica arranged perpendicular to the direction of the friction reduces surface contact while dissipating external force, thereby improving wear resistance. 3. The dendritic silica wires of the present invention have spherical particles, which can hinder the entanglement and agglomeration of fillers and improve dispersibility. The dendritic silica can connect the hydrophobic porous alumina hollow spheres to form a complete protective layer and a more effective wear-resistant layer. 4. The hydrophobic porous alumina hollow spheres and dendritic silica of the present invention are uniformly distributed in the nitrile rubber, and can absorb fracture energy when the nitrile rubber is subjected to tensile stress. In addition, the addition of the powder also introduces Si-OH bonds and strengthens the hydrogen bonding force of the rubber. DETAILED DESCRIPTION The present invention proposes a method for preparing a high heat-insulating and wear-resistant rubber. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example 1 The preparation method of hydrophobic porous alumina hollow spheres is as follows: (1) Take 200 mL of deionized water, 80 mL of anhydrous ethanol and 1 mL of aqueous ammonia, stir at 40°C for 60 min, add 1.4 g of phenol, 2.8 mL of formaldehyde, 0.6 g of lignin, 0.1 mL of aqueous ammonia and 0.45 g of polyvinyl alcohol, heat to 95°C while stirring for 15 h, add 0.34 g of hexamethylenetetramine, stir for 3 h, filter and separate, wash with water and dry; (2) placing the porous carbon spheres in a tubular furnace and calcining the spheres under a nitrogen atmosphere by heating the spheres to 300°C at a heating rate of 2°C / min and keeping the temperature for 30 min, then heating the spheres to 800°C at a heating rate of 5°C / min and keeping the temperature for 2 h, thereby obtaining porous carbon spheres; (3) Take 60 mL of 0.4 mol / L aluminum nitrate ethanol solution, add 0.2 g of porous carbon spheres, sonicate for 20 min, let stand for 8 h, filter and dry; (4) placing in a tube furnace, heating to 350°C and keeping the temperature for 2 h, then heating to 600°C and keeping the temperature for 4 h, and then cooling to obtain porous alumina hollow spheres; (5) Take 5 g of porous alumina hollow balls and 0.2 g of polymethylhydrogensiloxane, mix them evenly and add them to a ball mill. Use steel balls as the ball milling medium. The balls are: 1 Φ20 mm steel ball, 5 Φ10 mm steel balls, and 10 Φ6 mm steel balls. The main disk frequency is 40 Hz, and the ball milling is carried out for 30 min. (6) The product was repeatedly washed with petroleum ether, centrifuged until there was no free polymethylhydrogensiloxane in the supernatant, and vacuum dried at 60° C. to obtain hydrophobic porous alumina hollow spheres. Example 2 The preparation method of hydrophobic porous alumina hollow spheres is as follows: (1) Take 200 mL of deionized water, 80 mL of anhydrous ethanol and 1 mL of aqueous ammonia, stir at 40°C for 60 min, add 1.4 g of phenol, 2.8 mL of formaldehyde, 0.6 g of lignin, 0.1 mL of aqueous ammonia and 0.45 g of polyvinyl alcohol, heat to 95°C while stirring for 15 h, add 0.34 g of hexamethylenetetramine, stir for 3 h, filter and separate, wash with water and dry; (2) placing the porous carbon spheres in a tubular furnace and calcining the porous carbon spheres under a nitrogen atmosphere by heating the spheres to 300°C at a heating rate of 2°C / min and keeping the temperature for 30 min, then heating the spheres to 900°C at a heating rate of 5°C / min and keeping the temperature for 2 h, respectively; (3) Take 60 mL of 0.4 mol / L aluminum nitrate ethanol solution, add 0.2 g of porous carbon spheres, sonicate for 20 min, let stand for 8 h, filter and dry; (4) placing in a tube furnace, heating to 350°C and keeping the temperature for 2 h, then heating to 600°C and keeping the temperature for 4 h, and then cooling to obtain porous alumina hollow spheres; (5) Take 5 g of porous alumina hollow balls and 0.2 g of polymethylhydrogensiloxane, mix them evenly and add them to a ball mill. Use steel balls as the ball milling medium. The balls are: 1 Φ20 mm steel ball, 5 Φ10 mm steel balls, and 10 Φ6 mm steel balls. The main disk frequency is 40 Hz, and the ball milling is carried out for 30 min. (6) The product was repeatedly washed with petroleum ether, centrifuged until there was no free polymethylhydrogensiloxane in the supernatant, and vacuum dried at 60° C. to obtain hydrophobic porous alumina hollow spheres. Example 3 The preparation method of hydrophobic porous alumina hollow spheres is as follows: (1) Take 200 mL of deionized water, 80 mL of anhydrous ethanol and 1 mL of aqueous ammonia, stir at 40°C for 60 min, add 1.4 g of phenol, 2.8 mL of formaldehyde, 0.6 g of lignin, 0.1 mL of aqueous ammonia and 0.45 g of polyvinyl alcohol, heat to 95°C while stirring for 15 h, add 0.34 g of hexamethylenetetramine, stir for 3 h, filter and separate, wash with water and dry; (2) placing the mixture in a tubular furnace and calcining it in a nitrogen atmosphere, heating it to 300°C at a heating rate of 2°C / min, keeping it at that temperature for 30 min, and then heating it to 1000°C at a heating rate of 5°C / min, keeping it at that temperature for 2 h, to obtain porous carbon spheres; (3) Take 60 mL of 0.4 mol / L aluminum nitrate ethanol solution, add 0.2 g of porous carbon spheres, sonicate for 20 min, let stand for 8 h, filter and dry; (4) placing in a tube furnace, heating to 350°C and keeping the temperature for 2 h, then heating to 600°C and keeping the temperature for 4 h, and then cooling to obtain porous alumina hollow spheres; (5) Take 5 g of porous alumina hollow balls and 0.2 g of polymethylhydrogensiloxane, mix them evenly and add them to a ball mill. Use steel balls as the ball milling medium. The balls are: 1 Φ20 mm steel ball, 5 Φ10 mm steel balls, and 10 Φ6 mm steel balls. The main disk frequency is 40 Hz, and the ball milling is carried out for 30 min. (6) The product was repeatedly washed with petroleum ether, centrifuged until there was no free polymethylhydrogensiloxane in the supernatant, and vacuum dried at 60° C. to obtain hydrophobic porous alumina hollow spheres. Example 4 The preparation method of hydrophobic porous alumina hollow spheres is as follows: (1) Take 200 mL of deionized water, 80 mL of anhydrous ethanol and 1 mL of aqueous ammonia, stir at 40°C for 60 min, add 1.4 g of phenol, 2.8 mL of formaldehyde, 0.6 g of lignin, 0.1 mL of aqueous ammonia and 0.45 g of polyvinyl alcohol, heat to 95°C while stirring for 15 h, add 0.34 g of hexamethylenetetramine, stir for 3 h, filter and separate, wash with water and dry; (2) placing the porous carbon spheres in a tubular furnace and calcining the porous carbon spheres under a nitrogen atmosphere by heating the spheres to 300°C at a heating rate of 2°C / min and keeping the temperature for 30 min, then heating the spheres to 900°C at a heating rate of 5°C / min and keeping the temperature for 2 h, respectively; (3) Take 60 mL of 0.4 mol / L aluminum nitrate ethanol solution, add 0.2 g of porous carbon spheres, sonicate for 20 min, let stand for 8 h, filter and dry; (4) placing in a tube furnace, heating to 350°C and keeping the temperature for 2 h, then heating to 600°C and keeping the temperature for 4 h, and then cooling to obtain porous alumina hollow spheres; (5) Take 5 g of porous alumina hollow balls and 0.1 g of polymethylhydrogensiloxane, mix them evenly and add them to a ball mill. Use steel balls as the ball milling medium. The balls are: 1 Φ20 mm steel ball, 5 Φ10 mm steel balls, and 10 Φ6 mm steel balls. The main disk frequency is 40 Hz, and the ball milling is carried out for 30 min. (6) The product was repeatedly washed with petroleum ether, centrifuged until there was no free polymethylhydrogensiloxane in the supernatant, and vacuum dried at 60° C. to obtain hydrophobic porous alumina hollow spheres. Example 5 The preparation method of hydrophobic porous alumina hollow spheres is as follows: (1) Take 200 mL of deionized water, 80 mL of anhydrous ethanol and 1 mL of aqueous ammonia, stir at 40°C for 60 min, add 1.4 g of phenol, 2.8 mL of formaldehyde, 0.6 g of lignin, 0.1 mL of aqueous ammonia and 0.45 g of polyvinyl alcohol, heat to 95°C while stirring for 15 h, add 0.34 g of hexamethylenetetramine, stir for 3 h, filter and separate, wash with water and dry; (2) placing the porous carbon spheres in a tubular furnace and calcining the porous carbon spheres under a nitrogen atmosphere by heating the spheres to 300°C at a heating rate of 2°C / min and keeping the temperature for 30 min, then heating the spheres to 900°C at a heating rate of 5°C / min and keeping the temperature for 2 h, respectively; (3) Take 60 mL of 0.4 mol / L aluminum nitrate ethanol solution, add 0.2 g of porous carbon spheres, sonicate for 20 min, let stand for 8 h, filter and dry; (4) placing in a tube furnace, heating to 350°C and keeping the temperature for 2 h, then heating to 600°C and keeping the temperature for 4 h, and then cooling to obtain porous alumina hollow spheres; (5) Take 5 g of porous alumina hollow balls and 0.3 g of polymethylhydrogensiloxane, mix them evenly and add them to a ball mill. Use steel balls as the ball milling medium. The balls are: 1 Φ20 mm steel ball, 5 Φ10 mm steel balls, and 10 Φ6 mm steel balls. The main disk frequency is 40 Hz, and the ball milling is carried out for 30 min. (6) The product was repeatedly washed with petroleum ether, centrifuged until there was no free polymethylhydrogensiloxane in the supernatant, and vacuum dried at 60° C. to obtain hydrophobic porous alumina hollow spheres. The particle size, average pore size and hydrophobicity of the hydrophobic porous alumina hollow spheres prepared in the above examples were measured, and the results are shown in Table 1 below: Table 1 Particle size (nm) Average pore size (nm) Contact angle (°) Example 1 80-250 8-10 143.4 Example 2 50-200 5-7 143.8 Example 3 30-150 4-7 143.9 Example 4 50-200 5-7 136.7 Example 5 50-200 5-7 144.1 The hydrophobic porous alumina hollow spheres prepared in Example 5 were selected for subsequent experiments. Example 6 The preparation method of dendritic silica is as follows: (1) Dissolve 30 g of polyvinyl pyrrolidone in 320 mL of n-pentanol, add 28 mL of ethanol and 8 mL of water, shake evenly, then drop 3 mL of 0.18 mol / L sodium citrate dihydrate aqueous solution and mix evenly; (2) Add 5.5 mL of ammonia water while shaking, let it stand for 5 min, then add 2.8 mL of ethyl orthosilicate, shake evenly, and place at 90 °C for 3 h; (3) filtering with a polytetrafluoroethylene membrane having a pore size of 0.45 μm, washing with ethanol and water respectively, and then drying to obtain linear silica; (4) Take 2 g of linear silica, add 20 mL of ethanol and 6 mL of deionized water, add 0.22 g of dopamine hydrochloride, and adjust the pH to 8.5 with tris(hydroxymethyl)aminomethane; (5) Add 2 mL of ethyl orthosilicate and let stand at 30 °C for 24 h; (6) Filtering is performed using a polytetrafluoroethylene membrane with a pore size of 0.45 μm, and the mixture is washed with ethanol and water respectively and then dried to obtain dendritic silica. Example 7 A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: 12 parts of hydrophobic porous alumina hollow spheres and 8 parts of dendritic silica are mixed evenly, added into the open mill system in 2 equal portions, and mixed evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. Example 8 A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: 15 parts of hydrophobic porous alumina hollow spheres and 10 parts of dendritic silica were mixed evenly, added into the open mill system in two equal portions, and mixed evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. Example 9 A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: 18 parts of hydrophobic porous alumina hollow spheres and 12 parts of dendritic silica are mixed evenly, added into the open mill system in two equal portions, and mixed evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. Example 10 A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: 21 parts of hydrophobic porous alumina hollow spheres and 14 parts of dendritic silica were mixed evenly, added into the open mill system in two equal portions, and mixed evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. Embodiment 11 A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: 22.5 parts of hydrophobic porous alumina hollow spheres and 7.5 parts of dendritic silica were mixed evenly, added into the open mill system in two equal portions, and mixed evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. Example 12 A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: 15 parts of hydrophobic porous alumina hollow spheres and 15 parts of dendritic silica are mixed evenly, added into the open mill system in two equal portions, and mixed evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. Example 13 A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: 12.86 parts of hydrophobic porous alumina hollow spheres and 17.14 parts of dendritic silica were mixed evenly, added into the open mill system in two equal portions, and mixed evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. Comparative Example 1 The difference between this embodiment and embodiment 9 is that hydrophobic porous alumina hollow spheres are used instead of dendritic silica, specifically: A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: 30 parts of hydrophobic porous alumina hollow spheres are added into the open mill system in two equal portions and mixed evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. Comparative Example 2 The difference between this embodiment and embodiment 9 is that the hydrophobic porous alumina hollow spheres are replaced by dendritic silica, specifically: A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: Mix 30 parts of dendritic silica evenly, add it into the open mill system in 2 equal portions, and mix evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. Comparative Example 3 The difference between this embodiment and embodiment 9 is that porous alumina hollow spheres are added, specifically: A method for preparing high heat-insulating and wear-resistant rubber comprises the following steps: S1: 100 parts of nitrile rubber raw rubber were mixed and refined for 4 minutes at a temperature of 50°C, followed by addition of 5 parts of zinc oxide, 2 parts of stearic acid, 0.5 parts of microcrystalline wax, 2 parts of antioxidant RD and 1 part of antioxidant 445. S2: 18 parts of porous alumina hollow spheres and 12 parts of dendritic silica are mixed evenly, added into the open mill system in two equal portions, and mixed evenly; S3: Add 2 parts of accelerator TMTD and 1 part of sulfur, make triangle packs for multiple cycles, and then thinly pass through the sheets 6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat plate mold and vulcanized using a flat plate vulcanizer at a vulcanization temperature of 160°C for 25 minutes to obtain a highly heat-insulating and wear-resistant rubber. The preparation method of porous alumina hollow spheres is as follows: (1) Take 200 mL of deionized water, 80 mL of anhydrous ethanol and 1 mL of aqueous ammonia, stir at 40°C for 60 min, add 1.4 g of phenol, 2.8 mL of formaldehyde, 0.6 g of lignin, 0.1 mL of aqueous ammonia and 0.45 g of polyvinyl alcohol, heat to 95°C while stirring for 15 h, add 0.34 g of hexamethylenetetramine, stir for 3 h, filter and separate, wash with water and dry; (2) placing the porous carbon spheres in a tubular furnace and calcining the porous carbon spheres under a nitrogen atmosphere by heating the spheres to 300°C at a heating rate of 2°C / min and keeping the temperature for 30 min, then heating the spheres to 900°C at a heating rate of 5°C / min and keeping the temperature for 2 h, respectively; (3) Take 60 mL of 0.4 mol / L aluminum nitrate ethanol solution, add 0.2 g of porous carbon spheres, sonicate for 20 min, let stand for 8 h, filter and dry; (4) placing the mixture in a tubular furnace, heating it to 350°C and keeping it for 2 h, then heating it to 600°C and keeping it for 4 h, and then cooling it to obtain porous alumina hollow spheres. The thermal conductivity of high heat preservation and wear-resistant rubber is tested using a laser thermal conductivity meter; Abrasion is tested according to GB / T 9867-2008; According to GB / T 528-2009, the prepared high thermal insulation and wear-resistant rubber was cut into standard dumbbell-shaped specimens using a punching test machine, the thickness was measured with a vernier caliper, and the tensile strength was tested using an electronic universal testing machine. Table 2
Claims
1. A high heat-insulating and wear-resistant rubber, characterized in that: In parts by weight, it includes the following components: 100 parts of nitrile rubber Zinc oxide 5 parts 2 parts stearic acid 0.5 parts of microcrystalline wax 20-35 parts of thermal insulation and wear-resistant filler Anti-aging agent RD 2 parts Anti-aging agent 4451 parts Accelerator TMTD 2 parts 1 part sulfur; The heat-insulating and wear-resistant filler is a composite of hydrophobic porous alumina hollow balls and dendritic silicon dioxide.
2. The high heat-insulating and wear-resistant rubber according to claim 1, characterized in that: The mass ratio of the hydrophobic porous alumina hollow spheres to the dendritic silica is 3:(1-4).
3. The high heat-insulating and wear-resistant rubber according to claim 1, characterized in that: The preparation method of the hydrophobic porous alumina hollow spheres is as follows: (1) Take 200 mL of deionized water, 80 mL of anhydrous ethanol and 1 mL of aqueous ammonia, stir at 30-45° C. for 60 min, add 1.4 g of phenol, 2.8 mL of formaldehyde, 0.6 g of lignin, 0.1 mL of aqueous ammonia and 0.45 g of polyvinyl alcohol, heat to 95° C. for 15 h while stirring, add 0.34 g of hexamethylenetetramine, stir for 3 h, filter and separate, wash with water and dry; (2) placing in a tubular furnace, calcining in a nitrogen atmosphere, heating to 300°C at a heating rate of 2°C / min, keeping the temperature for 30 min, and then heating to 800-1000°C at a heating rate of 5°C / min, keeping the temperature for 2 h, to obtain porous carbon spheres; (3) Take 60 mL of 0.4 mol / L aluminum nitrate ethanol solution, add 0.2 g of porous carbon spheres, sonicate for 20 min, let stand for 8 h, filter and dry; (4) placing in a tube furnace, heating to 350°C and keeping the temperature for 2 h, then heating to 600°C and keeping the temperature for 4 h, and then cooling to obtain porous alumina hollow spheres; (5) Take 5 g of porous alumina hollow balls and 0.1-0.3 g of polymethylhydrogensiloxane, mix them evenly and add them into a ball mill, use steel balls as the ball milling medium, set the main disk frequency at 40 Hz, and ball mill for 30 min; (6) The product was repeatedly washed with petroleum ether, centrifuged until there was no free polymethylhydrogensiloxane in the supernatant, and vacuum dried at 60° C. to obtain hydrophobic porous alumina hollow spheres.
4. The high heat-insulating and wear-resistant rubber according to claim 3, characterized in that: The balls used for the ball milling in step (5) are: 1 Φ20 mm steel ball, 5 Φ10 mm steel balls, and 10 Φ6 mm steel balls.
5. The high heat-insulating and wear-resistant rubber according to claim 1, characterized in that: The preparation method of the dendritic silica is as follows: (1) Dissolve 30 g of polyvinyl pyrrolidone in 320 mL of n-pentanol, add 28 mL of ethanol and 8 mL of water, shake evenly, then drop 3 mL of 0.18 mol / L sodium citrate dihydrate aqueous solution and mix evenly; (2) Add 5.5 mL of ammonia water while shaking, let it stand for 5 min, then add 2.8 mL of ethyl orthosilicate, shake evenly, and place at 90°C to react for 2-3 h; (3) filtering with a polytetrafluoroethylene membrane, washing with ethanol and water respectively, and then drying to obtain linear silica; (4) Take 2 g of linear silica, add 20 mL of ethanol and 6 mL of deionized water, add 0.22 g of dopamine hydrochloride, and adjust the pH to 8.5 with tris(hydroxymethyl)aminomethane; (5) Add 2 mL of ethyl orthosilicate and let stand at 30 °C for 24 h; (6) Filter with a polytetrafluoroethylene membrane, wash with ethanol and water respectively, and then dry to obtain dendritic silica.
6. The high heat-insulating and wear-resistant rubber according to claim 5, characterized in that: The pore size of the polytetrafluoroethylene membrane in step (3) and step (6) is 0.45 μm.
7. A method for preparing a high heat-insulating and wear-resistant rubber according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: After refining the raw nitrile rubber, zinc oxide, stearic acid, microcrystalline wax, antioxidant RD and antioxidant 445 are added and mixed and refining is performed for 3-4 minutes; S2: Add the heat-insulating and wear-resistant filler into the open milling system in two batches and mix them evenly; S3: Add accelerator TMTD and sulfur, make triangle packs for multiple cycles, and then thin out the sheets 5-6 times, and place them for 12 hours to obtain the mixed rubber; S4: The mixed rubber is loaded into a flat mold and vulcanized using a flat vulcanizer at a vulcanization temperature of 160°C for 15-30 minutes to obtain a highly heat-insulating and wear-resistant rubber.
8. The method for preparing a high heat-insulating and wear-resistant rubber according to claim 7, characterized in that: The refining temperature in S1 is 50°C.
Citation Information
Cited By
Preparation method of PAN-based carbon fiber-copper powder brake disc
CN120438611A